Maternal health is the key to child health - Akhmadjonov Rafiqjon Toychiboy oglu; Akhmadjonova Sitorabonu Sodirjon qizi (Genius Journals, 2025)
This article provides information about the causes of disability. In particular, it was thought about the origin of various defects and the measures to prevent them as a result of the unfavorable course of the mother's pregnancy
Keywords: drugs; mechanical effects; chemical effects; environmental effects